2008
DOI: 10.1016/j.ejcts.2008.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Progress of the treatment for extended aortic aneurysms; is the frozen elephant trunk technique the next standard in the treatment of complex aortic disease including the arch?☆

Abstract: Patients with extensive aortic aneurysms involving the ascending aorta, aortic arch, and the descending aorta are still considered to be a challenge for many cardiovascular surgeons. The introduction of the elephant trunk technique by Borst et al. in 1983 has greatly facilitated surgery on this kind of pathology and this technique has been recognized as a standard modality for treatment of extended aortic aneurysms. As a next step, the frozen elephant trunk technique has been introduced in some institutes in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
2
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 58 publications
(107 reference statements)
1
39
2
3
Order By: Relevance
“…Inhospital mortality seems to be improved in comparison to the conventional ET (6.4% vs 10.2%, respectively) [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]. In a recent review published in 2008, FET has even been considered the standard treatment for extended aortic aneurysm as an alternative to conventional ET, as it allows for one-stage repair of combined aortic arch and proximal descending aortic aneurysm [60].…”
Section: Fet Techniquementioning
confidence: 97%
“…Inhospital mortality seems to be improved in comparison to the conventional ET (6.4% vs 10.2%, respectively) [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]. In a recent review published in 2008, FET has even been considered the standard treatment for extended aortic aneurysm as an alternative to conventional ET, as it allows for one-stage repair of combined aortic arch and proximal descending aortic aneurysm [60].…”
Section: Fet Techniquementioning
confidence: 97%
“…No cases of spinal cord ischemia have occurred in our patients since we began to use the blood-return procedure, but additional research on the pathogenesis of paraplegia after OSG is required. Karck and Kamiya,12) in a review of use of the frozen elephant trunk technique in 215 patients in eight series, reported a perioperative mortality rate of 7% (15 patients, including patients with acute aortic dissection). The overall perioperative mortality rate in our series was similar (6%), although the rate among our 44 patients who had elective surgery was lower (4%).…”
Section: Discussionmentioning
confidence: 99%
“…Abb. 5; [22]), um das perfundierte falsche Lumen möglichst langstreckig zu beseitigen [54,23]. Dies bedeutet jedoch für den einzelnen AADA-Patienten einen primär komplexeren operativen Eingriff mit einer längeren Herz-Kreislauf-Stillstandszeit sowie einer längeren myokardialen Ischämiezeit, verbunden mit einem erhöhten perioperativen Risiko.…”
Section: Operative Strategie Bei Aada Mit Aortenbogenbeteiligungunclassified